How Using a Restricted Grading Range Distorts GPAs and Disproportionately Penalizes Low-Performing Students - Wetzler, Elizabeth Leigh (Frontiers in Education, 2019)
This study evaluates how combining multiple grading practices and policies designed to promote excellence, differentiate among high-performing students, or prevent grade inflation at an elite institution affects GPA outcomes for low-performing students. The author evaluated archived performance data from 3,274 cadets completing a required course during a three-year period at the United States Military Academy (USMA) at West Point. Common grading practices use a restricted percentage range with a high cut-off value for the D category (67.0-69.9%), and, although used for other grades, USMA policy prohibits the use of plus/minus demarcations for the D grade in GPA calculations. Grade distributions were highly irregular, and, when combined with the lack of plus/minus demarcations for D’s in GPA calculations, the restricted D range in the grading scale resulted in disproportionate GPA penalties for low-performing students. These penalties masked other notable performance differences at higher levels. Recommendations include (a) conducting a benchmark study to determine the appropriate cut-off score for the current course and (b) conducting a comprehensive, retrospective review of cadets’ academic performance data across different courses and semesters to determine the percentage of cadets affected by the disproportionate penalty before deciding on a future course of action.